LABS: Laboratory Automation and Batch Scheduling – A Modular Open Source Python Program for the Control of Automated Electrochemical Synthesis with a Web Interface - Hielscher, Maximilian M.; Dörr, Maurice; Schneider, Johannes; Waldvogel, Siegfried R. (Chemistry, an Asian journal, 2023)
With LABS, an open source Python‐based lab software is established that enables users to orchestrate automated synthesis setups. The software consists of a user‐friendly interface for data input and system monitoring. A flexible backend architecture enables the integration of multiple lab devices. The software allows users to easily modify experimental parameters or routines and switch between different lab devices. Compared to previously published projects, we aim to provide a more widely applicable and easily customizable automation software for any experimental setup. The usefulness of this tool was demonstrated in the oxidative coupling of 2,4‐dimethyl‐phenol to the corresponding 2,2’‐biphenol. In this context, the suitable electrolysis parameters for flow electrolysis were optimized by way of design of experiments. We present LABS (Laboratory Automation and Batch Scheduling), a python‐based open source software that comes with a web‐based user interface. Our goal is to provide an easy to adapt software for laboratory automation and lay the foundation for many future automation projects. Its reliability was showcased during a campaign of an electrochemical C−C coupling reaction.